Assessing the Impacts of a Multi-Year Drought on Water Resources and Agriculture in the Aconcagua River Basin of Chile - Bellisario, Antonio; Janke, Jason (Investigaciones Geográficas: Una mirada desde el sur, 2024)
The Aconcagua watershed in Central Chile has experienced severe drought conditions for the past thirteen years, receiving only three-fifths of its average precipitation, marking the longest drought on record. Declining rainfall has led to widespread water shortages for agriculture and human consumption, while warmer temperatures have further reduced water availability, worsening the drought's impacts. This study examines the combined effects of decreasing precipitation, reduced streamflow, warmer temperatures, and changing agricultural land use patterns to assess the environmental impacts of the drought in the Aconcagua watershed. Trend analysis reveals that the drought, coupled with rising temperatures, has depleted the snowpack in the Andes, reducing river discharge and exacerbating a drying trend that diminishes regional water availability. Agriculture in the region, which depends almost exclusively on river discharge, has been severely impacted, with an average streamflow reduction of 59% since 2010 affecting arable land. Deficient irrigation infrastructure and inefficient water governance, combined with regional drying trends favored by climate change, are likely to worsen the situation. Addressing the drought in Chile requires a comprehensive and coordinated response from the government, civil society, and the private sector. This response should include measures to promote sustainable water use and conservation, support for affected communities and industries, and efforts to address the underlying drivers of the drought, including climate change and unsustainable practices.